2003
DOI: 10.1017/s0012162203000951
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of language regression in children

Abstract: The spectrum of language regression in childhood is incompletely understood. To describe the features of this disorder more fully, we reviewed the records of 196 consecutive children (143 males and 53 females) with language regression or perceived plateau evaluated between 1988 and 1994 by a child neurologist. Mean age at regression was 21.2 months and the mean interval to referral was 34.8 months. A trigger for the regression was identified in 74 of the children (38%) and was associated with a more rapid regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(62 citation statements)
references
References 32 publications
2
59
0
1
Order By: Relevance
“…Other symptoms, which are different from those observed in children with speech delay, are nonverbal communication disorders, stereotyped and persistent behaviors, restricted and/or unusual interests and impaired social interaction. 23 Our conclusion is that language regression in children is a severe disorder with significant longterm comorbidities. 24 Intervention in children with speech disorders Speech and language development may be appropriate or not, depending on chronological age.…”
Section: Delaymentioning
confidence: 87%
“…Other symptoms, which are different from those observed in children with speech delay, are nonverbal communication disorders, stereotyped and persistent behaviors, restricted and/or unusual interests and impaired social interaction. 23 Our conclusion is that language regression in children is a severe disorder with significant longterm comorbidities. 24 Intervention in children with speech disorders Speech and language development may be appropriate or not, depending on chronological age.…”
Section: Delaymentioning
confidence: 87%
“…Studies showed that 30% of the children with AR have clinical seizures (6,100,111). Interestingly, seizures in AR are more likely to occur in children who regress in language after age 3 (1,112,113).…”
Section: Autistic Regression and Esesmentioning
confidence: 99%
“…Language regression can occur in children with previously normal language development or may be in the form of a deterioration of the previously abnormal or delayed language skills (1,2).…”
Section: Introductionmentioning
confidence: 99%
“…Although both disorders share similar disease manifestations that are apparent postnatally, the timeline of their observable pathophysiology is intriguingly different. Children born with RTT have an initial 12-to 18-month period of normal development followed by intellectual regression (Wilson et al, 2003), whereas patients with AS have no observable window of normal development (Clayton-Smith, 1993).…”
Section: Neurodevelopmental Disorders: Angelman Syndromementioning
confidence: 99%